2019
DOI: 10.1111/nph.16133
|View full text |Cite
|
Sign up to set email alerts
|

DEGENERATED PANICLE AND PARTIAL STERILITY 1 (DPS1) encodes a cystathionine βsynthase domain containing protein required for anther cuticle and panicle development in rice

Abstract: Summary Degeneration of apical spikelets and reduced panicle fertility are common reasons for low seed‐setting rate in rice (Oryza sativa). However, little is known about the underlying molecular mechanisms. Here, we report a novel degenerated panicle and partial sterility 1 (dps1) mutant that showed panicle apical degeneration and reduced fertility in middle spikelets. dps1 plants were characterized by small whitish anthers with altered cuticle morphology and absence of pollen grains. Amounts of cuticular w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(82 citation statements)
references
References 70 publications
(121 reference statements)
1
81
0
Order By: Relevance
“…These results suggested that OsHSFA3-overexpressing plants had maintained ROS homeostasis and thus had lower oxidative damage. Enzymatic antioxidants play important roles in ROS scavenging for normal plant growth [13,38]. To estimate the ability of OsHSFA3-overexpressing Arabidopsis lines and WT to scavenge ROS, the activities of antioxidant enzymes, i.e., SOD, POD and CAT, were measured.…”
Section: Overexpression Of Oshsfa3 Increases Drought Tolerance By Decmentioning
confidence: 99%
See 2 more Smart Citations
“…These results suggested that OsHSFA3-overexpressing plants had maintained ROS homeostasis and thus had lower oxidative damage. Enzymatic antioxidants play important roles in ROS scavenging for normal plant growth [13,38]. To estimate the ability of OsHSFA3-overexpressing Arabidopsis lines and WT to scavenge ROS, the activities of antioxidant enzymes, i.e., SOD, POD and CAT, were measured.…”
Section: Overexpression Of Oshsfa3 Increases Drought Tolerance By Decmentioning
confidence: 99%
“…ABA levels were significantly higher in drought-stressed plants as compared to control plants ( Figure 5F). ABA content was higher in all transgenic lines than in WT plants after they were subjected to drought Enzymatic antioxidants play important roles in ROS scavenging for normal plant growth [13,38]. To estimate the ability of OsHSFA3-overexpressing Arabidopsis lines and WT to scavenge ROS, the activities of antioxidant enzymes, i.e., SOD, POD and CAT, were measured.…”
Section: Overexpression Of Oshsfa3 Increases Drought Tolerance By Decmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipid peroxidation was determined as malondialdehyde (MDA) content, measured by thiobarbituric (TBA) method using 'MDA Detection Kit (A003)' as described previously [27].…”
Section: Lipid Peroxidation and Ros Activitymentioning
confidence: 99%
“…The activities of enzymatic antioxidants were detected by using the commercial kits in accordance with the manufacturer's instructions as described earlier [27,28]. The kits for superoxide dismutase (A001), peroxidase (A084-3), catalase (A007-2), glutathione peroxidase (A005), glutathione reductase (A062), and glutathione S-transferase (A004) were purchased from the same company as mentioned above.…”
Section: Estimation Of Enzymatic and Non-enzymatic Antioxidantsmentioning
confidence: 99%